Paul and his social relations - Porter, Stanley E., 1956-; Land, Christopher D. (Leiden ; Boston : Brill, 2013)
This volume addresses many of the questions surrounding Paul and his social relations, including how to define and analyze such relations, their relationship to Paul's historical and social context, how Paul related to numerous friends and foes, and the implications for understanding Paul's letters as well as his theology.
Paul and his social relations : an introduction / Stanley E. Porter, Christopher D. Land -- How do we define Pauline social relations? / Stanley E. Porter -- Paul, Timothy, and Pauline individualism : a response to Bruce Malina / Mark Batluck -- Paul, patronage and benefaction : a "semiotic" reconsideration / Bruce A. Lowe -- Paul and the "social relations" of death at Rome (Romans 5:14, 17, 21) / James R. Harrison -- Relationships of Paul and Luke : Luke, Paul's letters, and the "we" passages of Acts / Sean A. Adams -- The authorship of Hebrews : a further development in the Luke-Paul relationship / Andrew W. Pitts, Joshua F. Walker -- The significance and function of references to Christians in the Pauline literature / Christoph Stenschke -- "We put no stumbling block in anyone's path, so that our ministry will not be discredited" : Paul's response to an idol food inquiry in 1 Corinthians 8:1-13 / Christopher D. Land -- Paul, the Corinthians' meal, and the social context / Panayotis Coutsoumpos -- The Christ-pattern for social relationships : Jesus as exemplar in Philippians and other Pauline epistles / Mark Keown -- Honouring Epaphroditus : a suffering and faithful servant worthy of admiration / H.H. Drake Williams, III.
Title from PDF title page (viewed on Dec. 3, 2012).
Includes bibliographical references and indexes.
Master record variable field(s) change: 630
Keywords: Paul, -- the Apostle, Saint -- Friends and associates; Bible. -- Criticism, interpretation, etc; Paul, -- the Apostle, Saint; Bible; RELIGION -- Biblical Biography -- New Testament; Friendship; Electronic books; Criticism, interpretation, etc; Electronic books